Aplikasi Pengenalan Koleksi Museum Lampung Berbasis Android - Shafina Azzahra; Febi Eka Febriansyah (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2019)
Lampung Museum is the largest museum in Lampung Province, in the formation of the history of Lampung Province so that its existence needs to be preserved. currently information technology is needed in every field. the number of visitors to the Lampung Museum 2011-2017 reached 70,000 visitors. In this study the application of the Introduction to Lampung Museum Collection based on Android can increase the interest of the Lampung community as well as foreign tourists to visit and see the Museum collection, the application is equipped with a barcode scan facility that allows visitors to search collection information. The results of the study have been successfully built an